StyleLink: User Identity Linkage Across Social Media with Stylometric Representations - Xu, Wenwen; Fung, Benjamin C. M. (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
User identity linkage (UIL) is the task of aligning user identities of the same user across different social network platforms. Although existing approaches have explored various aspects such as different user profile attributes and social network structures, the writing styles from user-generated texts, which is commonly known as stylometry, remain relatively underexplored. In this paper, we propose a novel Graph Neural Network (GNN)-based model named StyleLink, which leverages both social network structures and stylometric features derived from user-generated texts to address the UIL problem in an integrated manner. Our model utilizes GNNs to incorporate both stylometric features and the network structure for each social network, effectively embedding the network and enhancing user representation. This is the first work to incorporate stylometric features into GNNs to embed social networks and then conduct UIL between two embedding spaces. Extensive experiments on real-world social network datasets demonstrate the superior performance of StyleLink over existing state-of-the-art methods, achieving higher accuracy in user linkage and improved ranking of identity matches. In addition, we explore the effects of different linguistic characteristics in the identification of user identities and visualizes the effects of applying GNNs for better social network embedding.